What Happens to Workers at Firms that Automate? - Bessen, James; Goos, Maarten; Salomons, Anna; van den Berge, Wiljan (The Review of Economics and Statistics, 2025)
Abstract We estimate the impact of firm-level automation on individual worker outcomes by combining Dutch microdata with a direct measure of automation expenditures covering all private nonfinancial sector firms. Using a novel difference-in-differences event-study design leveraging lumpy investment, we find that automation increases the probability of incumbent workers separating from their employers. Workers experience a five-year cumulative wage income loss of 9% of one year’s earnings, driven by decreases in days worked. These adverse impacts of automation are larger in smaller firms, and for older and middle-educated workers. By contrast, no such losses are found for firms’ investments in computers.